MELPHALAN-INDUCED CYTOTOXICITY IN THE BONE MARROW OF RATS BY FLOW CYTOMETRY MEASUREMENTS - B I. Gerashchenko; I. M. Todor; O. O. Shevchuk; V. G. Nikolaev (International Journal of Medicine and Medical Research, 2019)
Background. Bone marrow (BM) that contains hematopoietic cells of various lineages is a sensitive target for a number of cytotoxic agents including chemotherapy drugs.